DENDRIMERS: A NOVEL TOOL FOR DRUG DELIVERY AND TARGETING - Chigbo, Udokwu Japhet; Ugochukwu, Adim Ekene; John, Dingwoke Francis (Universal Journal of Pharmaceutical Research, 2017)
Dendrimers are hyper-branched macromolecules having tree like structure, consisting of a core molecule and alternating layers of monomers. Due to their unique architecture these have improved physical and chemical properties like high solubility, miscibility and reactivity. Dendrimers consist of well defined size, shape, molecular weight and monodispersity. These properties formulate the dendrimers a suitable carrier in drug delivery application. These are built from number of molecular entities of colloidal particles that exists in equilibrium with the molecules or ions in nature and due to these increases the solubility of poorly soluble drugs. Dendrimers have the ability to encapsulate and bind the guest molecule can be used for solubility enhancement, sustained release and various drug delivery applications. The terminal groups are modified to attach biologically active substances for targeting purpose. Dendrimers are suitable for a wide range of targeted drug delivery, controlled drug delivery, gene delivery and industrial applications. This review gives concise information about the dendrimers, its synthesis, characterization and application in drug delivery. Peer Review History: Received 9 April 2017; Revised 12 May; Accepted 25 June, Available online 15 July 2017 Academic Editor: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Reviewer(s) detail: Dr. Areen Alshweiat , University of Szeged, Hungary, areen.alshweiat@hu.edu.jo Dr. Liliya Logoyda , Horbachevsky Ternopil State Medical University, Ukraine, logojda@tdmu.edu.ua